VALIDATION OF THE INSTRUMENT "PARENTAL SELF-EFFICACY IN CARING FOR FULL-TERM NEWBORNS: BRAZILIAN VERSION". - Soares da Silva, Lara Solano; Mandetta, Myriam Aparecida; Ferreira Gomes Balieiro, Maria Magda (Ciencia, Cuidado e Saude, 2023)
Objective: To validate the Preterm Parenting & Self-Efficacy Checklist Brazilian Version for use with parents of full-term newborns. Method: A methodological study carried out with 72 parents of full-term newborns attending a childcare program at a philanthropic institution in the city of São Paulo. Data was collected using the "Preterm Parenting & Self-Efficacy Checklist - Brazilian Version" and a questionnaire containing the parents' sociodemographic variables and perinatal variables. Cronbach's Alpha and factor analysis were used to analyze the data. Results: The majority of participants were women, with an average age of 28.5 years. The newborns had an average gestational age of 39 weeks, an average weight of 2940 grams and no complications at birth (98.6%). The internal consistency of the instrument was 0.808, the factor analysis showed that there was a correlation between the items and the factor loading value allowed the items of the original instrument to be maintained. The participants' parental self-efficacy was occasionally confident (mean 5.88). Conclusion: The instrument was consistent and reliable for use with parents of term newborns.